Photodynamic therapy for precancer diseases and cervical cancer (review of literature) - A. V. Gilyadova; Yu. S. Romanko; A. A. Ishchenko; S. V. Samoilova; A. A. Shiryaev; P. M. Alekseeva; K. T. Efendiev; I. V. Reshetov (Biomedical Photonics)
The paper presents the results of literature data analysis on the main directions of precancerous diseases of the cervix uteri and cervical cancer treatment. Side effects following surgery or radiation treatment can lead to structural deformities, scarring, hyperpigmentation, systemic side effects, and destruction of normal tissue. In addition, the use of traditional methods of treatment can cause multidrug resistance, which will lead to ineffective treatment and the development of a relapse of the disease. To avoid toxicity and reduce side effects, alternative treatment strategies have been proposed. Photodynamic therapy (PDT) is a promising organ-preserving highly selective method for treating cervical neoplasia, which includes two stages: the introduction of a photosensitizer and local exposure to directed light radiation. A number of studies have demonstrated the high clinical efficacy of this method in the treatment of patients with cervical neoplasia and carriage of human papillomavirus infection without adverse consequences for fertility. The use of PDT contributes to the successful outcome of the treatment of pathological foci on the mucous membrane of the cervix, the effectiveness and safety of the method is ensured by the selective effect on tissues. In the course of treatment, normal surrounding tissues are not damaged, there is no gross scarring and stenosis of the cervical canal, thereby PDT allows maintaining the normal anatomical and functional characteristics of the cervix.